If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(5x-2)+6=38
We simplify the equation to the form, which is simple to understand
4(5x-2)+6=38
Reorder the terms in parentheses
+(+20x-8)+6=38
Remove unnecessary parentheses
+20x-8+6=+38
We move all terms containing x to the left and all other terms to the right.
+20x=+38+8-6
We simplify left and right side of the equation.
+20x=+40
We divide both sides of the equation by 20 to get x.
x=2
| Cot(cos^-1(7x/8)) | | -3x^2+56x+29=0 | | 2x=5x-90 | | 15x+4=-2x+21 | | 3k^4+10k^3-48k^2=0 | | -3x^2+56t+29=0 | | (3w)w=300 | | 1/18=9.5/x | | 9-(2x-1)=45 | | 8x+4=4x+(-4) | | -5x+3.2=-3.2x+3.6 | | W/2=71 | | f(x)=(x+4)-25 | | 4x/9-7=1 | | .75(h+6)=15 | | 4x-2X+x+59= | | 12(z+2)-4(z-4)=3(z-1)+4(z-3) | | 10-d=-34+5d | | 5(n+8)=n+28 | | 8y+5/4=9y+1/4 | | -6x+3x=8-2x+4+16 | | x+y+x+y+2x+2z= | | 7x+2.0=-4x-5.3 | | 6(4x-9)-7=6(x-3)+65 | | 2x^2+24-60=0 | | 15x+20=20x-5 | | 6(4x-9)-7=6(x-3) | | x^2+6x+-55=0 | | .5(2x-2)=5x+4 | | f(x)=(x+6)-49 | | 48y^2-13y=0 | | -29=5(2a-1)+3 |